ANTIVIRAL COMPOUNDS AND PREPARATIONS EFFECTIVE AGAINST BOVINE VIRAL DIARRHEA - T. I. Glotova; A. A. Nikonova; A. G. Glotov (Вопросы вирусологии, 2017)
Bovine viral diarrhea virus (BVDV) belongs to the genus Pestivirus, family Flaviviridae. It causes various clinical forms of infection leading to significant economic losses in beef and dairy industry worldwide. Furthermore, the virus is a contaminant of biological preparations (bovine fetal serum, continuous cell cultures, vaccines for human and veterinary medicine, interferons, trypsin, biotechnological preparations, embryos, stem cells, etc.). It is used as a test object when developing methods of decontamination. In some countries, a tool for monitoring the infection caused by the virus is vaccination based on the use of live and inactivated vaccines with varying efficiency. The antiviral compounds are a potential means of control in case of insufficient efficacy of vaccines. Their advantage for BVDV control is the ability to provide immediate protection for animals at risk in the case of an outbreak of the disease. This review summarizes the current state of knowledge about antiviral compounds against BVDV. It was noted that due to the use of advanced biomedical technologies there is a tendency to search for drugs that might be effective for antiviral therapy of BVDV, as indicated by numerous studies of new compounds and the antiviral efficacy of known drugs used in medical practice. In addition to the well-known antiviral targets for the virus, such as the RdRp, IMPDH, NS3, new targets were discovered, such as protein p7. Its mechanism of action remains to be explored. It can be concluded that there is a great potential for BVDV control through the use of antiviral drugs which has not yet implemented. The biggest obstacle for commercial implementation of identified compounds is the lack of demonstration of their efficacy in vivo. Further studies should be performed to develop a method for administering effective drugs to groups of animals.